English translation of a classic handbook - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The cultivated plants of the Tropics and Subtropics by Sigmund Rehm and Gustav Espig 522pp 1991 ISBN 3 8236 1169 0 Verlag Josef Margraf Scientific Books also available from CTA